Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/pon.1056
|View full text |Cite
|
Sign up to set email alerts
|

The concept and measurement of meaning in life in Dutch cancer patients

Abstract: We investigated the psychometric properties of a Dutch translation of the Personal Meaning Profile in a heterogeneous group of cancer patients. Our study resulted in a relatively short scale consisting of 39 of the 57 original items, divided into 5 factors, labeled 'relation with God'; 'dedication to life'; 'fairness of life'; 'goal-orientedness' and 'relations with other people', which can be summed to a total score of the experience of meaning in life. The internal consistency of the total scale as well as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 37 publications
(43 reference statements)
5
43
0
2
Order By: Relevance
“…As older adults are more likely to maintain traditional gender roles and to be retired, cancer is more likely to disrupt women's opportunities for feeling useful than men's, for example, in doing housework such as cooking for their husbands. Similar to Jim et al [23] and Thompson and Pitts [40], but contrary to other studies [7,20,22,29], we did not find significant age differences in purpose in life. Most of the previous studies focused on cancer survivors, in which younger respondents had often resumed interrupted roles, such as wage-earner, and could derive meaning from them.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…As older adults are more likely to maintain traditional gender roles and to be retired, cancer is more likely to disrupt women's opportunities for feeling useful than men's, for example, in doing housework such as cooking for their husbands. Similar to Jim et al [23] and Thompson and Pitts [40], but contrary to other studies [7,20,22,29], we did not find significant age differences in purpose in life. Most of the previous studies focused on cancer survivors, in which younger respondents had often resumed interrupted roles, such as wage-earner, and could derive meaning from them.…”
Section: Discussionsupporting
confidence: 47%
“…As some studies found higher purpose in life in younger than in older cancer patients [7,20,22,29], in married as compared to unmarried patients [29,39], in men as compared to women [34], and-in samples not specific to cancer-in persons with higher socioeconomic status (SES) [30], we controlled for these variables in our multivariate analysis.…”
Section: Research Questionsmentioning
confidence: 99%
“…According to existentialist psychologists, meaning increases the quality of life and hope while mitigating the thought of suicide (Mascaro & Rosen, 2005;Dogra, Basu & Das, 2011). In other studies, meaning in life was found to be positively related to psychological well-being (De Klerk et al, 2009;Jaarsma, Pool, Ranchor & Sanderman, 2007), extraversion, adaptability, responsibility, and personal traits and negatively related to neurotic personal traits (Jaarsma et al, 2007). It is understood from the studies that the results regarding the relationship between meaning in life and sociodemographics are contradictory and no relationship was found in most studies (De Klerk et al, 2009).…”
Section: Meaning In Lifementioning
confidence: 92%
“…[16] For example, patients with cancer who are able to develop a sense of peace and equanimity in their cancer experience tend to have better quality of life [13,27] and better psychological health. [13,26,27,28,29] In children, spirituality has been defined as the ability to derive personal value and transcend beyond the self through relationships with others.…”
Section: Spirituality In Patients' Cancer Journeymentioning
confidence: 99%
“…[16] For example, patients with cancer who are able to develop a sense of peace and equanimity in their cancer experience tend to have better quality of life [13,27] and better psychological health. [13,26,27,28,29] In children, spirituality has been defined as the ability to derive personal value and transcend beyond the self through relationships with others. [30,15] As a result, Kamper R et al [15] searchers elucidates that children's view their parents as a "guardians" of sorts by downplaying symptoms, "acting" like they felt better, and having a cheerful demeanor as they protected their parents/family members.…”
Section: Spirituality In Patients' Cancer Journeymentioning
confidence: 99%